2006
DOI: 10.1128/aem.72.4.3032-3035.2006
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Dependent Bacterial Ecology: a Cautionary Tale

Abstract: Although laboratory dependence is an acknowledged problem in microbiology, it is seldom intensively studied or discussed. We demonstrate that laboratory dependence is real and quantifiable even in the popular model Escherichia coli. Here laboratory effects alter the equilibrium composition of a simple community composed of two strains of E. coli. Our data rule out changes in the bacterial strains, chemical batches, and human handling but implicate differences in growth medium, especially the water component.La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Anecdotal evidence from the present study suggests that attenuation occurs quickly in Tenacibaculum maritimum isolates (R. van Gelderen unpubl.). The cause of the non-pathogenic results of strain 89/4747 in the present study may be attenuation, but this requires further investigation as there are many other factors to consider, such as preservation techniques, age of isolate, culture media and storage over time (Michel & Garcia 2003, O'Keefe et al 2006.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Anecdotal evidence from the present study suggests that attenuation occurs quickly in Tenacibaculum maritimum isolates (R. van Gelderen unpubl.). The cause of the non-pathogenic results of strain 89/4747 in the present study may be attenuation, but this requires further investigation as there are many other factors to consider, such as preservation techniques, age of isolate, culture media and storage over time (Michel & Garcia 2003, O'Keefe et al 2006.…”
Section: Discussionmentioning
confidence: 89%
“…Anecdotal evidence from the present study suggests that attenuation occurs quickly in Tenacibaculum maritimum isolates (R. van Gelderen unpubl.). The cause of the non-pathogenic results of strain 89/4747 in the present study may be attenuation, but this requires further investigation as there are many other factors to consider, such as preservation techniques, age of isolate, culture media and storage over time (Michel & Garcia 2003, O'Keefe et al 2006.In contrast, strains 00/3280 and 89/4762 were highly virulent, resulting in 100% mortalities in 3 d. Both strains have previously been demonstrated as highly pathogenic (Carson et al 1992, Handlinger et al 1997, Powell et al 2004. Experimental application of Tenacibaculum maritimum to the gills of Atlantic salmon using strain 00/3280 caused high levels of mortalities within 48 h (Powell et al 2004).…”
mentioning
confidence: 89%
“…the commonly used sugar-based markers do not work because the prey culture medium we use contains various sugars; Sijtsma & Tan 1996). In addition, the use of markers can have other difficulties, for example in reliability (see O'Keefe et al 2006). In our assays, prey maximum growth rate at low density and long-term maximum population size indicate how well prey is able to respond to the addition of fresh resource and how efficiently resources are used to produce biomass in the long term, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, in our case we consider it more likely that the systematic discrepancy between fitness values is caused by a change in medium composition, which in turn has affected the relative reductive effect of each of the metals. YPD is a rich, undefined medium, and subtle changes in such media can have crucial consequences (Joho et al 1988;O'Keefe et al 2006;Corbacho et al 2011). In a pilot assay performed prior to this study, clone fitness correlated strongly with population fitness (data not shown).…”
Section: Appendix A2: Relative Fitness Of Evolved Clonesmentioning
confidence: 95%
“…That is, the same concentrations of Ni and Zn reduced overall yield (number of colonies after competition) more strongly in our current assays, while Cd had a smaller reductive effect. This difference in reductive effect may be due to subtle differences in the composition of our -undefined -media, which can have large consequences (Joho et al 1988;O'Keefe et al 2006;Corbacho et al 2011). Since we were unable to remedy this problem, we chose to correct our measurements for this effect.…”
Section: Assay Problemsmentioning
confidence: 99%